FINE ART AS A SOURCE OF THE FASHION SYSTEM - Кузнецова, І. О. (Art and Design, 2019)
Characterization and evaluation of the fashion system in the fine arts and its influence on the development of artistic images of different cultural eras. Methodology. The methods of systematization and updating of literary-analytical information of fine arts are used in the work. The accumulation, systematization and realization of project information were conducted by studying specialized professional literature on the properties of fine art as a source of the fashion system. Results. The fashion system is represented by different elements. The concept of influence of climatic features on the fashion system through the prism of fine arts is presented on the basis of the analysis of footwear. Examples of modern footwear are shown, based on the use of paintings by great masters. The stockings, hats, zibellino element as elements of the fashion system of the time in the fine arts have been considered in detail. It is proved that clothes, accessories, cosmetics, decorations and home accessories are fashion products in the fashion system and as a phenomenon of fashion have been represented in their historical development in works of art. It is proved that clothes, accessories, cosmetics, decorations and home accessories are fashionable products in the fashion system and as a phenomenon of fashion have been presented in their historical development in the works of art. The scientific novelty. The system of fashion in the context of its time in the visual arts is evaluated as a predictive characteristic, embedded in the visual arts that exist under the influence of climate, innovation and features of socio-political development of a certain society.